Jumlah al-Ismiyah al-Mansukhah dalam buku “al-Qira’ah ar-Rasyidah” Karya Abdul Fatah Shobri dan Ali Umar Juz 1 untuk kelas 2 KMI (Studi Sintaksis Deskriptif): Models of Education Based on the Merdeka Curriculum in the Department of Arabic Language Teaching at the State Islamic University of Prof. K.H Saifudin Zuhri Purwokerto - Ruswatie, Ade; Mukroji, Mukroji; Hafidz, Rif’an Ali; Fiqiyah, Maskanatul (University of Darussalam Gontor, 2024)
The educational process in the Arabic Language Education Department at the State Islamic University of Professor Kiai Haji Saifuddin Zuhri, Purwokerto, was conducted based on the Merdeka curriculum. This curriculum includes various models, such as the problem-based model, the project-based model, and the student-interest-based model. The educational process in the Arabic Language Education Department was carried out using the Merdeka curriculum, with several models depending on the teacher's capabilities. This research aimed to reveal the models used in the educational process based on the Merdeka curriculum. The researchers employed a qualitative approach in this study, which was a field study. They chose interviews, observations, and documentation to collect data. The data analysis method used was data reduction, presentation, and then drawing conclusions. After conducting the study, the researchers found that the models used in the educational process in the Arabic Language Education Department at the State Islamic University of Professor Kiai Haji Saifuddin Zuhri, Purwokerto, were project-based learning in some lessons, project-based learning in others, inquiry-based learning, discovery-based learning, and collaborative learning, which were applied frequently across all subjects in the Arabic Language Education Department.